b = -1
x₂ = -1
Объяснение:
x² + 2bx - 3 = 0
при x = 3:
9 + 6b - 3 = 0
6b = -6
x² - 2x - 3 = 0
D = (-2)² - 4*1*(-3) = 4 + 12 = 16
x₁ = (-b + √(D))/2a = (2 + 4)/2 = 3 (тот корень, который мы знаем)
x₂ = (-b - √(D))/2a = (2 - 4)/2 = -1 (второй корень)
b = -1
x₂ = -1
Объяснение:
x² + 2bx - 3 = 0
при x = 3:
9 + 6b - 3 = 0
6b = -6
b = -1
x² - 2x - 3 = 0
D = (-2)² - 4*1*(-3) = 4 + 12 = 16
x₁ = (-b + √(D))/2a = (2 + 4)/2 = 3 (тот корень, который мы знаем)
x₂ = (-b - √(D))/2a = (2 - 4)/2 = -1 (второй корень)